The Good, the Bad, and the Fungus: Insights into the Relationship Between Plants, Fungi, and Oomycetes in Hydroponics - Grace C. S. Laevens; William C. Dolson; Michelle M. Drapeau; Soufiane Telhig; Sarah E. Ruffell; Danielle M. Rose; Bernard R. Glick; Ashley A. Stegelmeier (Biology)
Hydroponic systems are examples of controlled environment agriculture (CEA) and present a promising alternative to traditional farming methods by increasing productivity, profitability, and sustainability. In hydroponic systems, crops are grown in the absence of soil and thus lack the native soil microbial community. This review focuses on fungi and oomycetes, both beneficial and pathogenic, that can colonize crops and persist in hydroponic systems. The symptomatology and mechanisms of pathogenesis for Botrytis, Colletotrichum, Fulvia, Fusarium, Phytophthora, Pythium, and Sclerotinia are explored for phytopathogenic fungi that target floral organs, leaves, roots, and vasculature of economically important hydroponic crops. Additionally, this review thoroughly explores the use of plant growth-promoting fungi (PGPF) to combat phytopathogens and increase hydroponic crop productivity; details of PGP strategies and mechanisms are discussed. The benefits of Aspergillus, Penicillium, Taloromyces, and Trichoderma to hydroponics systems are explored in detail. The culmination of these areas of research serves to improve the current understanding of the role of beneficial and pathogenic fungi, specifically in the hydroponic microbiome.